High-performance perovskite-polymer hybrid solar cells via electronic coupling with fullerene monolayers. - Abrusci, A; Stranks, S; Docampo, P; Yip, H; Jen, A; Snaith, H (2013)
A plethora of solution-processed materials have been developed for solar cell applications. Hybrid solar cells based on light absorbing semiconducting polymers infiltrated into mesoporous TiO2 are an interesting concept, but generating charge at the polymer-metal oxide heterojunction is challenging. Metal-organic perovskite absorbers have recently shown remarkable efficiencies but currently lack the range of color tunability of organics. Here, we have combined a fullerene self-assembled monolayer (C60SAM) functionalized mesoporous titania, a perovskite absorber (CH3NH3PbI3-xClx), and a light absorbing polymer hole-conductor, P3HT, to realize a 6.7% efficient hybrid solar cell. We find that photoexcitations in both the perovskite and the polymer undergo very efficient electron transfer to the C60SAM. The C60SAM acts as an electron acceptor but inhibits further electron transfer into the TiO2 mesostructure due to energy level misalignment and poor electronic coupling. Thermalized electrons from the C60SAM are then transported through the perovskite phase. This strategy allows a reduction of energy loss, while still employing a "mesoporous electron acceptor", representing an exciting and versatile route forward for hybrid photovoltaics incorporating light-absorbing polymers. Finally, we show that we can use the C60SAM functionalization of mesoporous TiO2 to achieve an 11.7% perovskite-sensitized solar cell using Spiro-OMeTAD as a transparent hole transporter.